Early Cognitive and Behavioral Deficits in Mouse Models for Tauopathy and Alzheimer’s Disease - Samaey, Celine; Schreurs, An; Stroobants, Stijn; Balschun, Detlef (Frontiers in Aging Neuroscience, 2019)
Neurocognitive disorders, among which Alzheimer’s disease (AD), have become one of the major causes of death in developed countries. No effective disease-modifying therapy is available, possibly because current treatments are administered too late to still be able to intervene in the disease progress. AD is characterized by a gradual onset with subclinical neurobiological and behavioral changes that precede diagnosis with years to even decades. The earlier the diagnosis, the earlier potential treatments can be tested and started. Mouse models are valuable to study the possible causes underlying early phases of neuropathology and their reflection in behavior and other biomarkers, to help improve preclinical detection and diagnosis of AD. Here, we assessed cognitive functioning and social behavior in transgenic mice expressing tau pathology only (Tau-P301L) or a combination of amyloid and tau pathology (APP-V717I x Tau-P301L). The mice were subjected to a variety of behavioral tasks at an age of 3-6 months, i.e. at an early phase of their AD-like pathology. We hypothesized that compared to age-matched wild-type controls, transgenic mice would show specific impairments in both cognitive and non-cognitive tasks. In line with our expectations, transgenic mice showed decreased cognitive flexibility in the Morris water maze, decreased exploratory behavior, decreased performance in a nesting task and increased anxiety-like behavior. In accordance with the amyloid-cascade hypothesis, some of the behavioral measures showed more severe deficits in APP-V717I x Tau-P301L compared to Tau-P301L mice, indicating an exacerbation of disease processes due to the co-occurrence of amyloid and Tau pathology. Our study supports the use of behavioral markers as early indicators of ongoing AD pathology during the preclinical phase.